Leonardo's machines : Da Vinci's inventions revealed - Taddei, Mario, ....-; Laurenza, Domenico, ....-; Zanon, Edoardo, ....- (Cincinnati (Ohio) : David and Charles, 2006)
Combining the original coded notebooks and modern computer imaging, over 30 of Leonardo da Vinci's inventions are pieced together in this work, in never-before-seen, mechanically accurate, computer generated artworks. Annotated diagrams show each working part of the contraptions, demonstrating in incredible detail how the machines would have operated. It also includes fascinating recreations of the finished inventions that show how they would have been used in contemporary life - from manned flying machines and mechanical bridges to musical instruments and devastating circular tanks. In-depth analysis of da Vinci's inventions reveal the stories that led to the finished designs.
Keywords: Leonardo da Vinci; Uitvindingen